FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PADA KANTOR KELURAHAN KADIDI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Riswandi, Riswandi; Darmawan, Darmawan (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
The objective of this study is to determine the effect of Work Facilities, Work Discipline, and Motivation on the Service Quality of the Kadidi Village Office Apparatus, Sidrap Regency. In this research, the method used is the quantitative analysis method which is implemented by using an analytical tool, namely Multiple Linear Regression. The results of the study can be concluded that: 1) that the work facilities are not correlated and have no effect on the quality of service of the apparatus, 2) the work discipline, both Korean, partial and simultaneous, has a significant relationship and has a significant effect on the service quality of the apparatus in PancaRijang Village, Sidenreng Regency. Rappang. 3) Work motivation, either in correlation or partially, is not related and affects Service Quality, although simultaneously it has a significant effect.